The Influence of Principals’ E-Leadership and Digital Competence on Teacher Performance at SMKS Kristen 1 Tomohon, Indonesia - Maliangkay, Jevie Jane; Tambingon, Henny Nikolin; Lengkong, Jeffry Sony Junus (International Journal of Information Technology and Education, 2026)
Digital transformation has altered the expectations placed on school leadership, instructional practice, and professional performance in vocational education. In this context, schools are increasingly required to integrate information and communication technology into management, communication, supervision, and classroom learning. This article develops a journal version of Jevie Jane Maliangkay’s master’s thesis on the influence of principals’ e-leadership and digital competence on teacher performance at SMKS Kristen 1 Tomohon, North Sulawesi, Indonesia. The purpose of the study was to examine: (1) the effect of principals’ e-leadership on teacher performance, (2) the effect of digital competence on teacher performance, and (3) the simultaneous effect of both variables on teacher performance. A quantitative explanatory design with a causal associative approach was employed. The study was conducted at SMKS Kristen 1 Tomohon from December 2025 to February 2026. Based on the detailed methodology and results sections of the thesis, the respondents comprised 30 teachers and the study used total sampling. Data were collected through structured questionnaires and analyzed using simple and multiple linear regression supported by SPSS. The data met the main analytical assumptions, including normality, linearity, and absence of multicollinearity. The results show that principals’ e-leadership had a positive and significant effect on teacher performance, with an effective contribution of about 14.3%. Digital competence also had a positive and significant effect and emerged as the dominant predictor. Simultaneously, the two independent variables significantly influenced teacher performance, with a coefficient of determination of about 59.6%, indicating that more than half of the variance in teacher performance could be explained by the model. The findings affirm that school digital leadership and digital competence are not merely technical matters; they are strategic determinants of instructional quality, work effectiveness, and professional accountability. The article argues that strengthening digital leadership, building teacher capacity, and embedding technology into organizational culture are central to improving performance in vocational secondary schools.